2003
DOI: 10.1046/j.1462-5822.2003.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

BFA-sensitive and insensitive exocytic pathways in Entamoeba histolytica trophozoites: their relationship to pathogenesis

Abstract: SummaryEntamoeba histolytica manifests its pathogenicity through several cellular processes triggered by external stimuli that activate signal transduction pathways. The intense secretory activity resulting from stimulation is not correlated with a typical endoplasmic reticulum (ER) or Golgi organization, and little is known in this parasite about endocytic/exocytic pathways. The interactions of trophozoites with fibronectin (FN) and cultured mammalian cells, which elicit secretory activities, were chosen to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…Although previous studies had detected antigens using antibodies against GA proteins such as €COP and ARF in vesicles of trophozoites that could be disrupted by Brefeldin A, GA functions per se had not (3,12). We now demonstrate that Eh has GA transporters for UDP-galactose and UDP-glucose.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although previous studies had detected antigens using antibodies against GA proteins such as €COP and ARF in vesicles of trophozoites that could be disrupted by Brefeldin A, GA functions per se had not (3,12). We now demonstrate that Eh has GA transporters for UDP-galactose and UDP-glucose.…”
Section: Discussionmentioning
confidence: 58%
“…Cryofixation and cryosubstitution studies showed flattened cisternae in the cytoplasm that resemble GA of higher eukaryotes (11). Antibodies against mammalian GA proteins such as €COP and ARF labeled vesicles of trophozoites that could be disrupted by Brefeldin A and okadaic acid, both known disrupters of GA structures of higher eukaryotes (3,12). Previously, a combination of cytochemical and transmission electron microscopy studies identified Eh vesicles with glucose-6-phosphatase and thiamine pyrophosphatase activities as well as vesicles fluorescently labeled with C6 -12-(N-methyl-N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl))-ceramide.…”
mentioning
confidence: 99%
“…Interestingly, it has been shown that export of newly synthesized proteins to the surface via secretory pathway is not actin-dependent, whereas trafficking in endocytic pathways is actin-dependent in Trypanosoma brucei (32). Although the secretory/endocytic pathway is not well characterized in Entamoeba histolytica, it has been shown that fibronectin receptor and Gal/GalNAc lectin trafficking to plasma membrane is brefeldin-A-dependent, whereas thiolproteinase secretion is brefeldin-A-independent in this parasite (33). Further characterization reveals that overexpression of a GTP-locked mutant of EhRabA alters ER morphology and mislocalizes Gal/GalNAc lectin without affecting the localization of other cell surface proteins, indicating the specific role of EhRabA in early secretory pathway (34).…”
mentioning
confidence: 99%
“…For example, in mammalian cells, this reagent can block egress of vesicles from the ER (21) and can induce vesicularization of Golgi apparata (11). In E. histolytica, BFA can alter the morphology of a population of Golgi-specific vesicles and inhibit the trafficking of a subset of secretory proteins (15). Interestingly, in E. histolytica, BFA also induces the formation of tubular structures that colocalize with an ER marker, protein disulfide isomerase (15).…”
Section: Vol 8 2009mentioning
confidence: 99%
“…In E. histolytica, BFA can alter the morphology of a population of Golgi-specific vesicles and inhibit the trafficking of a subset of secretory proteins (15). Interestingly, in E. histolytica, BFA also induces the formation of tubular structures that colocalize with an ER marker, protein disulfide isomerase (15). These structures are similar to those observed in the EhRabAQ84L-expressing cell line; therefore, we explored whether EhRabA might regulate vesicle trafficking pathways that are also sensitive to BFA treatment.…”
Section: Vol 8 2009mentioning
confidence: 99%